Future scenarios for earthquake and flood risk in Eastern Europe and Central Asia. Issue 7 (13th July 2017) - Murnane, R. J.; Daniell, J. E.; Schäfer, A. M.; Ward, P. J.; Winsemius, H. C.; Simpson, A.; Tijssen, A.; Toro, J.
Abstract: We report on a regional flood and earthquake risk assessment for 33 countries in Eastern Europe and Central Asia. Flood and earthquake risk were defined in terms of affected population and affected gross domestic product (GDP). Earthquake risk was also quantified in terms of fatalities and capital loss. Estimates of future population and GDP affected by earthquakes vary significantly among five shared socioeconomic pathways that are used to represent population and GDP in 2030 and 2080. There is a linear relationship between the future relative change in a nation's exposure (population or GDP) and its future relative change in annual average population or GDP affected by earthquakes. The evolution of flood hazard was quantified using a flood model with boundary conditions derived from five different general circulation models and two representative concentration pathways, and changes in population and GDP were quantified using two shared socioeconomic pathways. There is a nonlinear relationship between the future relative change in a nation's exposure (population or GDP) and its future relative change in its annual average population or GDP affected by floods. Six regions can be defined for positive and negative relative change in population that designate whether climate change can temper, counter, or reinforce relative changes in flood risk produced by changes in population or exposure. The departure from the one‐to‐one relationship between a relative change in a nation's population or GDP and its relative change in flood risk could be used to inform further efforts at flood mitigation and adaptation. Key Points: Future changes in modeled earthquake risk vary with socioeconomic pathway Future changes in modeled flood risk vary with global climate model, greenhouse gas emission scenario, and socioeconomic pathway Relative change in population affected by flooding can inform the selection of countries for further detailed risk analysis Plain Language Summary: Floods and earthquakes affect the economy and population of countries in Eastern Europe and Central Asia. Future changes in these countries' economies and population will change the impacts of floods and earthquakes. In addition, future changes in climate will change how often flooding occurs. We assume that earthquake occurrence won't change with climate changes. We show how much the economies and populations of these countries are affected by floods and earthquakes in 2015, 2030 and 2080. However, as we don't know for certain how the economies, population and climate will change in the future, we show result for a variety of scenarios for future economies, population and climate. We assess how future changes in the economy and population affect future flood risk using changes in earthquake risk, and assume the remaining change is caused by changes in climate. We suggest that for some countries the population affected by floods can increase even with a decrease in population, or the population affected by floods and decrease even with an increase in population, if the future change in flood hazard is sufficiently large.